Georgia : Technical Assistance Report-Draft Public Corporation Reform Strategy. (International Monetary Fund, 2021)
State-owned enterprises (SOEs) are a key part of Georgia's economy, accounting for a significant portion of GDP, employment and public investment. They deliver critical services in important economic sectors, including gas, electricity, water and transportation. Improving their performance is a critical step in the path to becoming a high income country. Since 2012, the authorities have been taking concrete steps to address challenges arising from the SOE sector. Substantial progress has been achieved in disclosing fiscal risks arising from SOEs in the Fiscal Risk Statement; increasing the monitoring capacity at the Ministry of Finance (MoF) by establishing a Fiscal Risk Management Unit (FRMU); rationalizing the number of SOEs; sectorizing them in line with international statistical standards; partially unwinding the role of the Partnership Fund; and restructuring some specific SOEs.